2012
DOI: 10.1242/jcs.092551
|View full text |Cite
|
Sign up to set email alerts
|

GBF1 (Gartenzwerg)-dependent secretion is required for Drosophila tubulogenesis

Abstract: SummaryHere we report on the generation and in vivo analysis of a series of loss-of-function mutants for the Drosophila ArfGEF, Gartenzwerg. The Drosophila gene gartenzwerg (garz) encodes the orthologue of mammalian GBF1. garz is expressed ubiquitously in embryos with substantially higher abundance in cells forming diverse tubular structures such as salivary glands, trachea, proventriculus or hindgut. In the absence of functional Garz protein, the integrity of the Golgi complex is impaired. As a result, both v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 81 publications
(106 reference statements)
1
36
0
Order By: Relevance
“…The deposition of chitin, the major component of aECM and other matrix proteins in the luminal space, is associated with the onset of diametric expansion [10][11][12]. The secretion process is associated with materials present in the tracheal cell cytoplasm that are released as a bolus into the lumen, via COP I-mediated and COP II-mediated vesicle trafficking between the endoplasmic reticulum (ER) and Golgi apparatus [13][14][15][16][17][18][19], and the Diaphanous-dependent secretory pathway [20]. These general secretory pathways are required for deposition of aECM components and the addition of membranes into the apical surface, which expands the luminal space.…”
Section: Tracheal Tube Maturation: Expansion and Elongationmentioning
confidence: 99%
“…The deposition of chitin, the major component of aECM and other matrix proteins in the luminal space, is associated with the onset of diametric expansion [10][11][12]. The secretion process is associated with materials present in the tracheal cell cytoplasm that are released as a bolus into the lumen, via COP I-mediated and COP II-mediated vesicle trafficking between the endoplasmic reticulum (ER) and Golgi apparatus [13][14][15][16][17][18][19], and the Diaphanous-dependent secretory pathway [20]. These general secretory pathways are required for deposition of aECM components and the addition of membranes into the apical surface, which expands the luminal space.…”
Section: Tracheal Tube Maturation: Expansion and Elongationmentioning
confidence: 99%
“…In order to remobilize the P-element in the Su(z)2 handC-GFP1.1 line on the second chromosome, a standard excision scheme was applied as described previously (Wang et al, 2012). Briefly, the line Su(z)2 handC-GFP1.1 was crossed to a homozygous viable and fertile transposase source in a piggyBac vector ( y 1 w 1118 ; PBac{Δ2-3.Exel}106, Bloomington Stock number 8200).…”
Section: Remobilization Of P-element By Transposase Mediated Excisionmentioning
confidence: 99%
“…One of the identified mutants, moon cheese, carries a mutation in the fly homolog of Membrin, an ER Golgi t-snare, and shows GFP negative vacuoles instead of continuous lumen in the cells of different branches -as if the newly made fragments of lumen were not able to fuse. Also, studies in the embryo have shown that both apical secretion and endocytosis are crucial for proper lumen expansion (Tsarouhas et al, 2007;Grieder et al, 2008;Jayaram et al, 2008;Forster et al, 2010;Norum et al, 2010;Armbruster and Luschnig, 2012;Wang et al, 2012). Interestingly, even in multicellular tubes the secretion that drives the enlargement of the apical membrane and leads to lumen expansion is regulated in a cell-autonomous manner (Forster et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed studies of the expansion process revealed that, at least in the embryo, deposition of a luminal matrix, the COP I/II secretion apparatus and septate junction proteins contribute to tube size regulation. To expand the diameter of the lumen, tracheal cells require proper apical secretion (Tsarouhas et al, 2007;Jayaram et al, 2008;Forster et al, 2010;Norum et al, 2010;Schottenfeld et al, 2010;Armbruster and Luschnig, 2012;Wang et al, 2012). Over-dilation of the tubes is prevented by a luminal matrix, formed by a chitin cable deposited into the growing luminal space and septate junction proteins.…”
Section: Introductionmentioning
confidence: 99%